Nanotoxicology in the context of the safety evaluation of gold nanoparticles - Rito, Margarida do Rosário (2022)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2021, Universidade de Lisboa, Faculdade de Farmácia.